Spanish DAL: A Spanish Dictionary of Affect in Language - Gravano, A. (2014)
The topic of sentiment analysis in text has been extensively studied in the English language for the past 30 years. An early, influential work by Cynthia Whissell, the Dictionary of Affect in Language (DAL), allows rating words along three dimensions: pleasantness, activation and imagery. Given the lack of such tools in Spanish, we decided to replicate Whissell’s work in that language. This report describes the Spanish DAL, a Spanish lexicon formed by more than 2500 words manually rated by humans along the same three dimensions. We evaluated its usefulness on two sentiment analysis tasks, which showed that our lexicon managed to capture relevant information regarding the three affective dimensions.